Impact of iron overload on poor graft function after allo-HSCT in a patient with transfusion-dependent low-risk MDS: A case report and literature review. Issue 51 (23rd December 2022) - Wang, Cong; Zhao, Munan; Nie, Yuanyuan; Yang, Yan; Tan, Yehui; Du, Zhonghua; Gao, Sujun; Li, Wei
Abstract : Rationale: Poor graft function (PGF) occurs in 5% to 27% of allogeneic hematopoietic stem cell transplantation (allo-HSCT) and is associated with high life-threatening complications. The etiology of PGF is complex and multifactorial, and iron overload (IOL) is considered as a predictive factor. Patient concern: A 45-years-old woman who was diagnosed as low-risk myelodysplastic syndrome in 2012 has been transfusion dependent and developed severe IOL. Diagnoses: Due to transfusion dependency and also ineffective erythropoiesis, this patient was diagnosed as IOL and developed PGF after allo-HSCT. Interventions: Deferasirox (20mg/kg/d) was administered regularly after allo-HSCT for 2 years. Outcomes: Hematopoiesis was gradually recovered during iron chelation therapy treatment after allo-HSCT and PGF was reverted. Lessons: IOL, as a prognostic factor for PGF, is a common problem in Transfusion dependent myelodysplastic syndrome patients undergoing HSCT. IOL issues should be considered at the time of diagnosis and throughout the treatment course for patients who are potential candidates for HSCT.